An investigation on oil of rubber seed (Hevea brasiliensis) - Njoku Obioma U; Ononogbu I C; Owusu Ansah J Y
Oil from seeds of Hevea brasiliensis traditionally used as thickening agent for source preparation was isolated, and its physical and chemical characteristics determined. Saponification yielded saturated and unsaturated fatty acids which were seperated by preferential crystallization using organic solvents. Methanol, Ethanol, Hexane and Acetone were found effective solvents in this regard. Gas liquid chromatography (GLC) revealed large amounts of C18 fatty acids as well as traces of other fatty acids. The iodine values show that the solvents used in this study gave excellent yields of fatty acids with acetone being the most effective as a crystallization solvent to oil ratio 3:1 at 5degreeC.
Keywords: Chemical composition; Fatty acid composition; Rubber seed oil